Effect of Reducing Agents on Physical and Chemical Properties of Silver Nanoparticles - Roto Roto; Hani Prima Rasydta; Adhitasari Suratman; Nurul Hidayat Aprilita (Indonesian Journal of Chemistry, 2018)
Silver nanoparticles having uniform size and shape, a diameter range of 10–50 nm, excellent stability, and high zeta potential are always desirable for many applications. The silver nanoparticles were synthesized by chemical reduction method using some reducing agents in a polyvinyl alcohol solution. This study aims at determining the effect of reducing agents on the chemical and physical properties of silver nanoparticles. Ascorbic acid, sodium borohydride, hydrazine, sodium citrate, and glucose were used as reducing agents. Surface Plasmon Resonance (SPR) absorbance, morphology, zeta potential, crystal system, and stability of the products were studied. The results showed that the chemical and physical properties of the colloidal Ag nanoparticles were dependent on the reducing agents. In general, the produced silver nanoparticles have an fcc crystal system with a unit cell of 4.0906–4.0992 Å. The SPR absorbance of the colloids has the peak in the range of 401–433 nm. We found that the colloid of silver nanoparticles prepared by using ascorbic acid has uniform spherical shape, the diameter of about 20 nm, and zeta potential of -10.4 mV. After being stored for one month, the SPR absorbance of the colloid decreased by only 5%. This type of colloidal Ag nanoparticles prepared by using ascorbic acid is expected to be used for chemical sensors, an antibacterial agent, and so on.